Male football players have better patient-reported outcomes after primary anterior cruciate ligament reconstruction compared with females - Anne Fältström; Martin Hägglund; Joanna Kvist (BMC, 2024)
Abstract Background Sex differences in patient-reported outcomes (PROs) are not well investigated after anterior cruciate ligament (ACL) reconstruction in football players. The aim was to study sex differences in player-related factors, ACL injury characteristics and PROs after primary ACL reconstruction in football players. Methods In this cross-sectional cohort study a survey was sent to 390 male and 403 female football players who were injured when playing football and had undergone a primary ACL reconstruction in the previous 1-3 years. Player-related factors, ACL injury characteristics, and PROs covering knee function, satisfaction with activity level and knee function, and readiness to return to sport were compared between male and females. The questionnaires International Knee Documentation Committee Subjective Knee Evaluation Form (IKDC-SKF), Knee injury and Osteoarthritis Outcome Score (KOOS), ACL-Quality of Life (ACL-QoL) and ACL-Return to Sport after Injury (ACL-RSI) were used. Results Ninety males (23%) and 283 (70%) females answered the survey, 65 males and 198 females fulfilled the inclusion criteria. Males had returned to football to a higher degree (77% vs 59%, p = 0.008) at any time after ACL reconstruction, but at the time of the survey, an equal number of males and females played football (55% vs 47%, p = 0.239) and had similar activity level according to the Tegner Activity Score (median, 9; interquartile range [IQR], 7, vs median, 8; IQR, 7; p = 0.740). Males were more satisfied with their knee function and activity level and rated higher scores in the IKDC-SKF (mean ± standard deviation, 83 ± 16 vs 76 ± 16, p = 0.006), KOOS Sport/Recreation (79 ± 19 vs 72 ± 22, p = 0.034), KOOS Quality of Life (73 ± 22 vs 64 ± 20, p = 0.008), ACL-QoL (7.6 ± 2 vs 6.8 ± 1.8, p = 0.008), and ACL-RSI (6.7 ± 2.1 vs 5.5 ± 2.3, p < 0.001) than females (all with small − medium effect sizes). Conclusions Male football players reported more favourable results than females in patient-reported knee function, satisfaction with activity level and knee function, knee-related quality of life and psychological readiness to return to sport 1-3 years after ACL reconstruction. The results contribute to a better understanding of the eventual effect of patient sex on outcomes after ACL reconstruction in football players. However, the clinical importance of these differences is unclear.